Evaluation of the technical skills of the nursing staff in attending cardiopulmonary arrest (Research, Society and Development, 2021)
Cardiorespiratory arrest is one of the factors responsible for the increase in morbidity and mortality, even in situations or places that can guarantee an ideal care. The aim of this study is to assess the knowledge and technical skills of the nursing team regarding cardiopulmonary resuscitation. This is a quantitative, descriptive, cross-sectional study. Developed in an Emergency Care Unit in a city in the interior of São Paulo. From July to August 2020. The sample was 32 participants. Instruments were developed to collect sociodemographic data, and which evaluated performance; as skills and attitudes of the professional, as well as theoretical and practical knowledge on the subject addressed, being built according to the literature and protocols of care of the American Heart Association. The data were analyzed using descriptive statistical analysis. Most participants are female (27; 84.4%), aged between 20 and 30 years (14; 43.8%), Nursing Technicians (15; 46.9%). Regarding the result of the Knowledge Test on Cardiopulmonary Resuscitation, composed of 15 true or false statements, an issue with 100% correct answers was observed by the participants. There is a deficit and gaps in the knowledge of the nursing staff in the care of cardiopulmonary resuscitation.